Energetic Proton Spectra Measured by the Van Allen Probes. Issue 10 (17th October 2017) - Summers, Danny; Shi, Run; Engebretson, Mark J.; Oksavik, Kjellmar; Manweiler, Jerry W.; Mitchell, Donald G.
Abstract: We test the hypothesis that pitch angle scattering by electromagnetic ion cyclotron (EMIC) waves can limit ring current proton fluxes. For two chosen magnetic storms, during 17–20 March 2013 and 17–20 March 2015, we measure proton energy spectra in the region 3 ≤  L  ≤ 6 using the RBSPICE‐B instrument on the Van Allen Probes. The most intense proton spectra are observed to occur during the recovery periods of the respective storms. Using proton precipitation data from the POES (NOAA and MetOp) spacecraft, we deduce that EMIC wave action was prevalent at the times and L ‐shell locations of the most intense proton spectra. We calculate limiting ring current proton energy spectra from recently developed theory. Comparisons between the observed proton energy spectra and the theoretical limiting spectra show reasonable agreement. We conclude that the measurements of the most intense proton spectra are consistent with self‐limiting by EMIC wave scattering. Key Points: Proton energy spectra are measured by the Van Allen Probes for two magnetic storms The most intense proton spectra are compared with theoretical limiting spectra Observations of the most intense proton spectra are consistent with self‐limiting by EMIC wave scattering